2020
DOI: 10.1111/iwj.13348
|View full text |Cite
|
Sign up to set email alerts
|

Depression in diabetic foot ulcer: Associated factors and the impact of perceived social support and anxiety on depression

Abstract: Diabetic foot ulcer (DFU) exerts a heavy physical and emotional burden on patients with diabetes mellitus. The purpose of the present study was to explore the impact of anxiety and perceived social support on depression of DFU patients well as patients' characteristics associated with depression. The sample of the study consisted of 180 DFU patients. Data collected by the completion of “Self‐rating Depression/Anxiety Scale‐ Zung” (SDS/SAS) and the Multidimensional Scale of Perceived Social Support (MSPSS). Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…The level of HbA1c reflected the adherence characteristics of DFU patients; adherence characteristics were verified in previous study as important factors of QoL in diabetic patients (22). Polikandrioti et al also found that the decrease of social support was significantly related to the increase of depression in DFU patients and the presence of depression would further affect the QoL of patients (18). Most importantly, low psychological resilience was identified as an important risk factor of QoL in DFU participants in our study, which is similar to how it has been shown to influence patients with other diseases (13,14).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The level of HbA1c reflected the adherence characteristics of DFU patients; adherence characteristics were verified in previous study as important factors of QoL in diabetic patients (22). Polikandrioti et al also found that the decrease of social support was significantly related to the increase of depression in DFU patients and the presence of depression would further affect the QoL of patients (18). Most importantly, low psychological resilience was identified as an important risk factor of QoL in DFU participants in our study, which is similar to how it has been shown to influence patients with other diseases (13,14).…”
Section: Discussionsupporting
confidence: 56%
“…There were different grades of foot ulcer among the participants in our study, most of whom had grade 1 or grade 2 foot ulcers. Generally, most DFU participants were diagnosed with a grade of less than 4 according to a previous study (1,18). However, conditions graded as such will still incur a significant decrease in the QoL of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that functional social support referring to the help and encouragement that is provided to individuals by their social network played an important role in medication adherence ( 49 ). Higher social support is related to better psychological health and better health outcomes ( 50 , 51 ), indicating that higher social support has more positive emotion and health behaviors, which may be an explanation for why higher social support is associated with better adherence to some extent. Furthermore, in a qualitative study, patients reported that their spouses or other caregivers provided practical support by directly helping and supervising their medication, which is important to increase their medication adherence ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies had shown that this scale exhibited excellent psychometric properties in different cultures and were widely used in different countries [18][19][20][21]. It can be applied not only to healthy people but also to various clinical patients such as diabetes [22], breast cancer, autism and mental disorders. In brief, the PSSS is an adaptable instrument for evaluating perceived social support in a variety of samples.…”
Section: Introductionmentioning
confidence: 99%